The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00787-013-0384-z
|View full text |Cite
|
Sign up to set email alerts
|

Mental health problems and recidivism among detained male adolescents from various ethnic origins

Abstract: This study examines differences in self-reported mental health problems between detained youths from Dutch, Moroccan, and Surinamese origin and the usefulness of mental health problems to predict violent and property recidivism in these juveniles. A sample of 296 detained boys aged between 12 and 18 years were assessed by means of the Strengths and Difficulties Questionnaire (SDQ). Official information regarding criminal history and recidivism was collected 3-6 years later. In general, Dutch youths and Surinam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
28
5
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 35 publications
9
28
5
3
Order By: Relevance
“…They also experienced more often poly-victimization. These results are in line with both general population samples and incarcerated samples (Abram et al, 2004;Colins et al, 2013;Wood, Foy, Layne, Pynoos, & James, 2002). Also, internalizing symptoms such as depressive mood, self-harm and suicidal thoughts and internalizing disorders were significantly more prevalent in antisocial adolescent females than in adolescent males, as confirmed by the literature (e.g., Abram et al, 2004;Kerig et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…They also experienced more often poly-victimization. These results are in line with both general population samples and incarcerated samples (Abram et al, 2004;Colins et al, 2013;Wood, Foy, Layne, Pynoos, & James, 2002). Also, internalizing symptoms such as depressive mood, self-harm and suicidal thoughts and internalizing disorders were significantly more prevalent in antisocial adolescent females than in adolescent males, as confirmed by the literature (e.g., Abram et al, 2004;Kerig et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…Ethnic minorities showed less internalizing symptoms than Dutch antisocial adolescents. This might be due to underreporting of the mental health problems, or selection criteria in referring youth to the outpatient forensic clinic (e.g., Colins et al, 2013). The results at least warrant further study of the backgrounds and pathways to outpatient treatment of different ethnic groups.…”
Section: Discussionmentioning
confidence: 91%
“…Third, nonindigenous boys were overrepresented in the juvenile justice system and consequently, the majority of the participants had a non‐Dutch ethnic background. Nonindigenous youths have been found to have a tendency to underreport mental health problems for various reasons (Colins et al, ; Zwirs et al, ) that are out of the scope of the present study. However, a study on the Dutch version of the MAYSI‐2 revealed that Moroccan juveniles indeed reported fewer mental health problems, but this could not be explained by differences in measurement reliability, as the MAYSI‐2 was found to be a reliable instrument across ethnic groups (Colins et al, ).…”
Section: Discussionmentioning
confidence: 81%
“…Besides common indicators of juvenile delinquent and risk behaviors, such as low socio-economic status (SES) and age (e.g., DeLisi, Neppl, Lohman, Vaughn, & Shook, 2013;Kipping, Smith, Heron, Hickman, & Campbell, 2015), we added foreign nationality as a covariate because Switzerland has been shown to have high rates of migration, and previous research indicated that juveniles with foreign nationalities were overrepresented in the Swiss justice system (Killias, 2009). Moreover, further European studies showed that JSOs with foreign nationalities differed from domestic adolescent delinquents in regard to social and health adversities (e.g., Aebi et al, 2012;Bauer et al, 2011;Colins et al, 2013).…”
Section: Patterns Of Adverse Childhood Experiencesmentioning
confidence: 99%